Flexible Bioelectronic Devices Based on Micropatterned Monolithic Carbon Fiber Mats. Issue 2 (11th December 2019) - Vomero, Maria; Gueli, Calogero; Zucchini, Elena; Fadiga, Luciano; Erhardt, Johannes B.; Sharma, Swati; Stieglitz, Thomas
Abstract: Polymer‐derived carbon can serve as an electrode material in multimodal neural stimulation, recording, and neurotransmitter sensing platforms. The primary challenge in its applicability in implantable, flexible neural devices is its characteristic mechanical hardness that renders it difficult to fabricate the entire device using only carbon. A microfabrication technique is introduced for patterning flexible, cloth‐like, polymer‐derived carbon fiber (CF) mats embedded in polyimide (PI), via selective reactive ion etching. This scalable, monolithic manufacturing method eliminates any joints or metal interconnects and creates electrocorticography electrode arrays based on a single CF mat. The batch‐fabricated CF/PI composite structures, with critical dimension of 12.5 µm, are tested for their mechanical, electrical, and electrochemical stability, as well as to chemicals that mimic acute postsurgery inflammatory reactions. Their recording performance is validated in rat models. Reported CF patterning process can benefit various carbon microdevices that are expected to feature flexibility, material stability, and biocompatibility. Abstract : A microfabrication technique for patterning flexible, cloth‐like, polymer‐derived carbon fiber mats embedded in polyimide is introduced. This scalable, monolithic manufacturing method eliminates any joints or metal interconnects and creates electrocorticography electrode arrays based on a single carbon fiber mat. Implantable neural electrode arrays with a thickness of 12.5 µm show good recording performance in rat models.